Efektivitas Penggunaan Model Latihan Kebugaran “Bbc Exercise” Untuk Pemeliharaan Kebugaran Jasmani Mahasiswa - Bile, Robertus Lili; Suharharjana, Suharharjana (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2019)
ABSTRACTThe problem of physical fitness is still a global pandemic which is increasingly widespread in many circles of society. Singentari lifestyle is one of the factors causing health problems such as degenerative diseases, decreased physical fitness, injury prone, decreased cognitive function and so on. Students with a relatively high level of activity tend to ignore regular sports activities so that it has an impact on the low level of physical fitness. This study aims to test the effectiveness of using a fitness training product in the form of a “BBC Exercise” model for maintenance of physical fitness. This research was conducted at STKIP Citra Bakti Ngada, involving 15 students with an age range ≤19 years as research subjects. The research design used was a pre-experimental time series with a one group pretest-posttest design. Data were collected by measuring physical fitness using the TKJI format (Indonesian Physical Fitness Test). The results of the pretest-posttest difference test obtained the sig value. (2-tailed) paired samples t-test (0.000) is smaller than (0.05) or (p <0.05). This means that there is a significant effect of using the "BBC Exercise" model on changes in the physical fitness categories of students. Thus, it is concluded that the use of the "BBC Exercise" exercise model is proven to be "effective" in increasing physical fitness. ABSTRAKPermasalahan kebugaran jasmani hingga kini masih menjadi pandemi global yang semakin meluas pada banyak kalangan masyarakat. Pola hidup sendentari menjadi salah satu faktor penyebab timbulnya gangguan kesehatan seperti penyakit degeneratif, kebugaran jasmani menurun, rentan cedera, penurunan fungsi kognitif dan lain sebagainya. Mahasiswa dengan tingkat kesibukan yang relatif tinggi cenderung mengabaikan aktivitas olahraga reguler sehingga berdampak pada rendahnya tingkat kebugaran jasmani. Penelitian ini bertujuan untuk menguji efektivitas penggunaan sebuah produk latihan kebugaran berupa model “BBC Exercise” untuk pemeliharaan kebugaran jasmani. Penelitian ini dilakukan di STKIP Citra Bakti Ngada, melibatkan 15 mahasiswa dengan rentang usia ≤19 tahun sebagai subjek penelitian. Desain penelitian yang digunakan adalah pra-eksperimen time series dengan rancangan one group pretest-posttest. Data dikumpulkan dengan tes pengukuran kebugaran jasmani menggunakan format TKJI (Tes Kesegaran Jasmani Indonesia). Hasil uji beda pretest-posttest diperoleh nilai sig. (2-tailed) paired samples t-test (0,000) lebih kecil dari (0,05) atau (p<0,05). Hal ini berarti bahwa terdapat pengaruh yang signifikan penggunaan model “BBC Exercise” terhadap perubahan kategori kebugaran jasmani mahasiswa. Dengan demikian disimpulkan bahwa penggunaan model latihan “BBC Exercise” terbukti “Efektif” meningkatkan kebugaran jasmani.